Melawan Prasangka dalam Kontestasi Politik: Kajian Psikologi Politik Islam - saliyo, saliyo (State Islamic Institute of Kudus (IAIN Kudus), 2018)
This article has the purpose of integrating Western theories with the teachings of Islam. The theory is the theory of prejudice in political psychology with Islamic teachings in the al-Qur'an and Hadist. The both al-Quran and Hadist are the two main sources of the study of Islamic psychology. The prejudice of terms in political psychology is compatible with the terms suu dhon and khusnu dhon in Islamic political psychology.This research includes literature research. The research included the category of qualitative research.The analysis used with Deductive inductive analysis. The work of researchers in data collection and analysis involves six stages: the first, researchers look for material information related to the subject. The second explores the themes that are appropriate to the theme chosen by the researcher. The Thirdly, the analysis of existing knowledge information is repeated. The Fourth, an unnecessary reduction of data. The fifth verification data by the researcher. The sixth conducted a discussion of the theme findings. Finally make a conclusion.The results of the study show that political behavior in political psychology or Islamic political psychology is the origin of behavior that can lead to conflict, mobs and can enter legal institutions. Discipline, maturity, and being a person in politics can be seen when one can be cautious in applying bias in public places. The effects of the application of the theory of psychological prejudice can be seen from anxiety, emotions, division strategies, human needs for achievement, affiliation, and power.Keywords: Prejudice, Political Contestation, and Islamic Political Psychology.